Protecting the future: Fatal incidents on Australian farms involving children (2001‐2019). (9th August 2020) - Peachey, Kerri‐Lynn; Lower, Tony; Rolfe, Margaret
Abstract: Objectives: To assess the demographic and causal factors, plus trends in rates of fatal farm incidents involving children (<15 years) in Australia over the 2001‐2019 period. Design: A descriptive retrospective epidemiological study of the National Coronial Information System. Setting: Australia. Participants: Cases involving children (<15 years), where incidents have occurred on a farm (1 January 2001‐31 December 2019). Results: There has been essentially no change in the fatality rate for farm‐related child injury deaths across Australia in the 2001‐2019 period (−0.009/year). Men and children aged 0‐4 years were significantly more likely to be involved in these incidents. Most cases were recreational in nature (81%), with seven agents (water bodies, quads [all‐terrain vehicles], tractors, utes, cars, motorbikes and horses), accounting for 75% of cases. Water bodies were responsible for over 31% of deaths. Conclusion: The lack of progress addressing child farm injury mortality requires urgent attention. The overall rates and pattern of injury‐related deaths have stagnated, necessitating new and innovative approaches to address the issue. The emerging National Injury Prevention Plan might provide scope to improve the focus on and implementation of evidence‐based approaches.